A calibration-free capacitive moisture detection method for multiple soil environments. (March 2021) - Deng, Xiao; Yang, Lei; Fu, Zijian; Du, Chao; Lyu, Huafang; Cui, Liqin; Zhang, Li; Zhang, Jun; Jia, Bin
Highlights: Proposed a calibration-free moisture detection method for multiple soils. Analyzed structure and performance of capacitance sensor by finite element method. A temperature compensation algorithm was used to calibrate the capacitance sensor. The relationship between sand content and capacitance-water model was investigated. Abstract: The traditional soil moisture sensors need to be recalibrated for different soil types. It is not conducive to large-scale applications because of the complex calibration algorithm and expensive equipment. In this paper, a capacitive sensor was designed based on the difference of dielectric constant caused by the variation of water content in soil. The effect of structural parameters of sensor on its performance was analyzed by finite element method. The optimized sensor was evaluated in the air-drying experiment of five soil samples for four cycles. According to the relationship between capacitance-water model and sand content, a simple calibration-free detection model was proposed for multiple soil environments. The accuracy of the model was discussed by three repetitive experiments, and compared with the standard oven-drying method. The results show that MAME and RMSE of CWM-four model are 3.8% and 2.0%, respectively, which can basically meet the accuracy requirement for the field application.